A kind of EVA injection molding supercritical physical foaming material and preparation method thereof

By rationally formulating components in EVA injection molding supercritical physical foaming materials and foaming under supercritical conditions, the problem of insufficient performance of existing EVA foaming materials is solved, and hardness, tensile strength and compression back are achieved. Improved elastic performance.

CN119019781BActive Publication Date: 2025-02-18JINJIANG SHIDA PLASTIC FINE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411507229.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

It is difficult for existing EVA foaming materials to combine good hardness, tensile strength and compression rebound properties.

Method used

The supercritical physical foaming material is formed by using EVA injection molding. By reasonably preparing components such as zinc oxide glue, adhesive and foaming agent, and foaming treatment under supercritical conditions, a material with excellent performance is formed.

Benefits of technology

It has achieved significant improvements in the hardness, tensile strength and compression resilience of EVA foamed materials, meeting the needs of high-performance soles and interior materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to an EVA injection molding supercritical physical foaming material and a preparation method thereof, belonging to the field of polymer materials, wherein the EVA injection molding supercritical physical foaming material comprises the following components in parts by weight: 30-40 parts of EVA, 10-20 parts of polybutylene adipate terephthalate, 10-15 parts of adhesive, 6-8 parts of AC foaming agent, 12-16 parts of zinc oxide glue, 5-8 parts of dodecyltrimethylammonium chloride, 20-30 parts of calcium carbonate, 2-4 parts of dicumyl peroxide, 60-80 parts of water and 1-2 parts of zinc stearate. The EVA injection molding supercritical physical foaming material prepared by the present invention has excellent hardness, tensile strength and compression resilience.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, and in particular to an EVA injection molding supercritical physical foaming material and a preparation method thereof. Background Art

[0002] Ethylene-vinyl acetate copolymer (EVA) is a copolymer of ethylene and vinyl acetate. EVA has a wide range of applications. EVA foam materials have properties such as softness, good elasticity, and chemical corrosion resistance. They are used in the soles and interior materials of mid-to-high-end tourist shoes, hiking shoes, slippers, and sandals. However, existing EVA foam materials are difficult to have good hardness, tensile strength, and compression resilience. Summary of the invention

[0003] In view of this, the object of the present invention is to provide an EVA injection molding supercritical physical foaming material and a preparation method thereof, which has excellent hardness, tensile strength and compression rebound performance.

[0004] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: an EVA injection molding supercritical physical foaming material, comprising the following components in parts by weight: 30-40 parts of EVA, 10-20 parts of polybutylene adipate terephthalate, 10-15 parts of adhesive, 6-8 parts of AC foaming agent, 12-16 parts of zinc oxide glue, 5-8 parts of dodecyltrimethylammonium chloride, 20-30 parts of calcium carbonate, 2-4 parts of diisopropylbenzene peroxide, 60-80 parts of water and 1-2 parts of zinc stearate.

[0005] Preferably, the EVA injection molding supercritical physical foaming material comprises the following components in parts by weight: 35 parts of EVA, 15 parts of polybutylene adipate terephthalate, 12.5 parts of adhesive, 7 parts of AC foaming agent, 14 parts of zinc oxide glue, 6.5 parts of dodecyltrimethylammonium chloride, 25 parts of calcium carbonate, 3 parts of diisopropylbenzene peroxide, 70 parts of water and 1.5 parts of zinc stearate.

[0006] Preferably, the preparation method of the adhesive comprises the following steps:

[0007] S11: In an inert gas atmosphere, 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine are mixed uniformly, and reacted at 60-80° C. for 6-8 hours to obtain a reaction mixture;

[0008] S12: The reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid are uniformly mixed, and reacted at 160-180° C. for 6-8 hours to obtain an adhesive.

[0009] Preferably, the weight ratio of the 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine is 1:3:4.

[0010] Preferably, the weight ratio of the reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid is 1:2:3:5.

[0011] Preferably, the preparation method of the zinc oxide glue is:

[0012] Evenly mix gelatin, 50% triethanolamine aqueous solution, caprolactam, zinc acetate and silane coupling agent, and react at 60-75°C for 1-2h to obtain zinc oxide glue.

[0013] Preferably, the weight ratio of the gelatin, 50% by mass aqueous solution of triethanolamine, caprolactam, zinc acetate and silane coupling agent is 1:5:2:2:1.

[0014] The present invention also provides a method for preparing an EVA injection molding supercritical physical foaming material, which is used to prepare the EVA injection molding supercritical physical foaming material, comprising the following steps:

[0015] S1: EVA, polybutylene adipate terephthalate, adhesive, AC foaming agent, zinc oxide glue, dodecyltrimethylammonium chloride, calcium carbonate, dicumyl peroxide, water and zinc stearate are mixed evenly and stirred for 20-30 minutes, added into the hopper of a twin-screw extruder for melt extrusion, and injected into a mold cavity through an injection molding device to obtain a blank;

[0016] S2: Put the blank into a high-pressure nitrogen autoclave, add high-pressure carbon dioxide gas and high-pressure nitrogen with a purity of 99%-99.99%, react in an environment with a pressure of 16-28Mpa, maintain the material temperature in the autoclave at 70-100℃ for 1-2h and then take it out to obtain EVA injection molding supercritical physical foaming material.

[0017] Preferably, in step S1, the temperatures of various zones of the twin-screw extruder are 60°C, 70°C, 75°C, 85°C, and 90°C, respectively, and the screw speed is 14-16 r / min.

[0018] Preferably, in step S1, the material pipe temperature of the injection molding equipment is 80-100°C, and the mold temperature is 100-110°C.

[0019] The invention has the following beneficial effects: the zinc oxide of the invention is modified by gelatin to improve the dispersion and adhesion of regular nanoparticles, and is cross-linked with a coupling agent to form a long flexible glue chain structure, and then the strong hydrogen bonding of the sulfonic acid and amide groups provides adhesion for the zinc oxide glue liquid, and at the same time, the long flexible chain segment is grafted onto the sulfonated polyimide group, so that the rigidity of the component can be effectively improved, and the flexibility of the polymer-colloid mixed component is further improved. In addition, the introduced sulfonated group can form a stronger conjugation effect between the molecular chains, and at the same time, the sulfonic acid group is used as a cross-linking point, so that the molecular entanglement effect brought about by the molecular entanglement effect improves the deformation resistance of the melt, and the more obvious strain hardening phenomenon is conducive to resisting the tensile stress of the pore growth, thereby reducing the stress concentration during foaming, and preventing the excessive surface tension from hindering the growth of the pores. In addition, during the supercritical foaming process, the foaming agent, calcium carbonate and polymer interact with each other, and the supercritical gas has a large swelling effect on the polymer-colloid molecular chain, which increases the free volume of the polymer-colloid, improves the mobility of the molecular chain, enhances the plasticizing ability of the polymer, and greatly reduces the melt strength of the foaming beads, thereby improving the hardness, tensile strength and compression rebound properties of the foaming material. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In addition, it is specifically stated that the raw materials and equipment of the present invention can be obtained from commercial sources, and no longer listed one by one. Among them, the raw materials of the present invention can be obtained from commercial sources and are well known to those skilled in the art.

[0021] Embodiment 1: An EVA injection molding supercritical physical foaming material comprises the following components in parts by weight: 40 parts of EVA, 20 parts of polybutylene adipate terephthalate, 15 parts of adhesive, 8 parts of AC foaming agent, 16 parts of zinc oxide glue, 8 parts of dodecyltrimethylammonium chloride, 30 parts of calcium carbonate, 4 parts of diisopropylbenzene peroxide, 80 parts of water and 2 parts of zinc stearate.

[0022] In this embodiment, the preparation method of the adhesive comprises the following steps:

[0023] S11: In an inert gas atmosphere, 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine were mixed uniformly in a weight ratio of 1:3:4, and reacted at 80° C. for 8 h to obtain a reaction mixture;

[0024] S12: The reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid are uniformly mixed in a weight ratio of 1:2:3:5, and reacted at 180° C. for 8 hours to obtain an adhesive.

[0025] In this embodiment, the preparation method of the zinc oxide glue is:

[0026] Gelatin, 50% triethanolamine aqueous solution, caprolactam, zinc acetate and silane coupling agent were uniformly mixed in a weight ratio of 1:5:2:2:1, and reacted at 75°C for 2h to obtain zinc oxide glue.

[0027] This embodiment also provides a method for preparing an EVA injection molding supercritical physical foaming material, which is used to prepare the EVA injection molding supercritical physical foaming material, comprising the following steps:

[0028] S1: EVA, polybutylene adipate terephthalate, adhesive, AC foaming agent, zinc oxide glue, dodecyltrimethylammonium chloride, calcium carbonate, dicumyl peroxide, water and zinc stearate are mixed evenly and stirred for 30 minutes, and then added into the hopper of a twin-screw extruder for melt extrusion, wherein the temperatures of the various zones of the twin-screw extruder are 60° C., 70° C., 75° C., 85° C. and 90° C., respectively, and the screw speed is 16 r / min, and injected into the mold cavity through an injection molding device, wherein the material pipe temperature of the injection molding device is 100° C., and the mold temperature is 110° C., to obtain a blank;

[0029] S2: Put the blank into a high-pressure nitrogen autoclave, add high-pressure carbon dioxide gas and high-pressure nitrogen with a purity of 99.99%, react in an environment with a pressure of 28Mpa, maintain the material temperature in the autoclave at 100℃ for 2h and then take it out to obtain EVA injection molding supercritical physical foaming material.

[0030] Embodiment 2: An EVA injection molding supercritical physical foaming material comprises the following components in parts by weight: 30 parts of EVA, 10 parts of polybutylene adipate terephthalate, 10 parts of adhesive, 6 parts of AC foaming agent, 12 parts of zinc oxide glue, 5 parts of dodecyltrimethylammonium chloride, 20 parts of calcium carbonate, 2 parts of diisopropylbenzene peroxide, 60 parts of water and 1 part of zinc stearate.

[0031] In this embodiment, the preparation method of the adhesive comprises the following steps:

[0032] S11: In an inert gas atmosphere, 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine were mixed uniformly in a weight ratio of 1:3:4, and reacted at 60° C. for 6 h to obtain a reaction mixture;

[0033] S12: The reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid are uniformly mixed in a weight ratio of 1:2:3:5, and reacted at 160° C. for 6 hours to obtain an adhesive.

[0034] In this embodiment, the preparation method of the zinc oxide glue is:

[0035] Gelatin, 50% triethanolamine aqueous solution, caprolactam, zinc acetate and silane coupling agent were uniformly mixed in a weight ratio of 1:5:2:2:1, and reacted at 60°C for 1 hour to obtain zinc oxide glue.

[0036] This embodiment also provides a method for preparing an EVA injection molding supercritical physical foaming material, which is used to prepare the EVA injection molding supercritical physical foaming material, comprising the following steps:

[0037] S1: EVA, polybutylene adipate terephthalate, adhesive, AC foaming agent, zinc oxide glue, dodecyltrimethylammonium chloride, calcium carbonate, dicumyl peroxide, water and zinc stearate are mixed evenly and stirred for 20 minutes, and then added into the hopper of a twin-screw extruder for melt extrusion, wherein the temperatures of the zones of the twin-screw extruder are 60° C., 70° C., 75° C., 85° C. and 90° C., respectively, and the screw speed is 14 r / min, and injected into the mold cavity through an injection molding device, wherein the material pipe temperature of the injection molding device is 80° C., and the mold temperature is 100° C., to obtain a blank;

[0038] S2: Put the blank into a high-pressure nitrogen autoclave, add high-pressure carbon dioxide gas and high-pressure nitrogen with a purity of 99%, react in an environment with a pressure of 16Mpa, maintain the material temperature in the autoclave at 70°C for 1 hour and then take it out to obtain EVA injection molding supercritical physical foaming material.

[0039] Embodiment 3: An EVA injection molding supercritical physical foaming material comprises the following components in parts by weight: 35 parts of EVA, 15 parts of polybutylene adipate terephthalate, 12.5 parts of adhesive, 7 parts of AC foaming agent, 14 parts of zinc oxide glue, 6.5 parts of dodecyltrimethylammonium chloride, 25 parts of calcium carbonate, 3 parts of diisopropylbenzene peroxide, 70 parts of water and 1.5 parts of zinc stearate.

[0040] In this embodiment, the preparation method of the adhesive comprises the following steps:

[0041] S11: In an inert gas atmosphere, 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine were mixed uniformly in a weight ratio of 1:3:4, and reacted at 70° C. for 7 h to obtain a reaction mixture;

[0042] S12: The reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid are uniformly mixed in a weight ratio of 1:2:3:5, and reacted at 170° C. for 7 hours to obtain an adhesive.

[0043] In this embodiment, the preparation method of the zinc oxide glue is:

[0044] Gelatin, 50% triethanolamine aqueous solution, caprolactam, zinc acetate and silane coupling agent were uniformly mixed in a weight ratio of 1:5:2:2:1, and reacted at 70°C for 1.5h to obtain zinc oxide glue.

[0045] This embodiment also provides a method for preparing an EVA injection molding supercritical physical foaming material, which is used to prepare the EVA injection molding supercritical physical foaming material, comprising the following steps:

[0046] S1: EVA, polybutylene adipate terephthalate, adhesive, AC foaming agent, zinc oxide glue, dodecyltrimethylammonium chloride, calcium carbonate, dicumyl peroxide, water and zinc stearate are mixed evenly and stirred for 25 minutes, and then added into the hopper of a twin-screw extruder for melt extrusion, wherein the temperatures of the various zones of the twin-screw extruder are 60° C., 70° C., 75° C., 85° C. and 90° C., respectively, and the screw speed is 15 r / min, and injected into the mold cavity through an injection molding device, wherein the material pipe temperature of the injection molding device is 90° C., and the mold temperature is 105° C., to obtain a blank;

[0047] S2: Put the blank into a high-pressure nitrogen autoclave, add high-pressure carbon dioxide gas and high-pressure nitrogen with a purity of 99.5%, react in an environment with a pressure of 22Mpa, maintain the material temperature in the autoclave at 85℃ for 1.5h and then take it out to obtain EVA injection molding supercritical physical foaming material.

[0048] Comparative Example 1: The difference from Example 3 is that no adhesive is added.

[0049] Comparative Example 2: The difference from Example 3 is that zinc oxide is used to replace the zinc oxide glue.

[0050] Comparative Example 3: The difference from Example 3 is that no adhesive is added, and zinc oxide is used to replace the zinc oxide glue.

[0051] The hardness, tensile strength and compression deformation tests were performed on the products prepared in Examples 1-3 and Comparative Examples 1-3. The test results are shown in Table 1.

[0052] Among them, the hardness test method is: the sample thickness is cut into 4mm, and the hardness of the material is tested according to GB / T 531.1-2008, using LX-C Shore hardness tester;

[0053] Tensile strength test method: The specimen is dumbbell-shaped, and the tensile strength of the material is tested according to GB / T 6344-2008, with a tensile speed of 500 mm / min.

[0054] Compression deformation test method: Cut the sample into a size of 20mm*20mm*10mm, and refer to HG / T 2876-2009 to test the permanent deformation of the material under compression, with a compression rate of 50%, a temperature of 50°C, and a time of 6 hours.

[0055] Table 1 Test results of products of Examples 1-3 and Comparative Examples 1-3:

[0056]

[0057] It can be seen from Table 1 that the EVA foam material prepared by the present invention has excellent hardness, tensile strength and compression resilience.

[0058] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An EVA injection molding supercritical physical foaming material, characterized in that: The invention comprises the following components in parts by weight: 30-40 parts of EVA, 10-20 parts of polybutylene adipate terephthalate, 10-15 parts of adhesive, 6-8 parts of AC foaming agent, 12-16 parts of zinc oxide glue, 5-8 parts of dodecyltrimethylammonium chloride, 20-30 parts of calcium carbonate, 2-4 parts of dicumyl peroxide, 60-80 parts of water and 1-2 parts of zinc stearate; The preparation method of the adhesive comprises the following steps: S11: In an inert gas atmosphere, 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine are mixed uniformly, and reacted at 60-80° C. for 6-8 hours to obtain a reaction mixture; the weight ratio of the 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine is 1:3:4; S12: uniformly mixing the reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid, and reacting at 160-180° C. for 6-8 hours to obtain an adhesive; the weight ratio of the reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid is 1:2:3:5; The preparation method of the zinc oxide glue is: Evenly mix gelatin, a 50% by mass aqueous solution of triethanolamine, caprolactam, zinc acetate and a silane coupling agent, and react at 60-75° C. for 1-2 hours to obtain a zinc oxide glue solution; the weight ratio of the gelatin, the 50% by mass aqueous solution of triethanolamine, caprolactam, zinc acetate and the silane coupling agent is 1:5:2:2:

1.

2. The EVA injection molding supercritical physical foaming material according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 35 parts of EVA, 15 parts of polybutylene adipate terephthalate, 12.5 parts of adhesive, 7 parts of AC foaming agent, 14 parts of zinc oxide glue, 6.5 parts of dodecyltrimethylammonium chloride, 25 parts of calcium carbonate, 3 parts of diisopropylbenzene peroxide, 70 parts of water and 1.5 parts of zinc stearate.

3. A method for preparing an EVA injection molding supercritical physical foaming material, used for preparing the EVA injection molding supercritical physical foaming material as claimed in claim 1, characterized in that: The following steps are involved: S1: EVA, polybutylene adipate terephthalate, adhesive, AC foaming agent, zinc oxide glue, dodecyltrimethylammonium chloride, calcium carbonate, dicumyl peroxide, water and zinc stearate are mixed evenly and stirred for 20-30 minutes, added into the hopper of a twin-screw extruder for melt extrusion, and injected into a mold cavity through an injection molding device to obtain a blank; S2: Put the blank into a high-pressure nitrogen autoclave, add high-pressure carbon dioxide gas and high-pressure nitrogen with a purity of 99%-99.99%, react in an environment with a pressure of 16-28Mpa, maintain the material temperature in the autoclave at 70-100℃ for 1-2h and then take it out to obtain EVA injection molding supercritical physical foaming material.

4. The method for preparing the EVA injection molding supercritical physical foaming material as claimed in claim 3, characterized in that: In step S1, the temperatures of the various zones of the twin-screw extruder are 60°C, 70°C, 75°C, 85°C, and 90°C, respectively, and the screw speed is 14-16 r / min.

5. The method for preparing the EVA injection molding supercritical physical foaming material as claimed in claim 3, characterized in that: In step S1, the material pipe temperature of the injection molding equipment is 80-100°C, and the mold temperature is 100-110°C.

Citation Information

Patent Citations

  • High-performance EVA foam material with uniform foam pore distribution and preparation method thereof

    CN111909439A

  • Cationic polyester cotton superfine denier four-way stretch fabric and preparation process thereof

    CN118292288A